Chushingura (the treasury of loyal retainers) a puppet play - Takeda, Izumo 1691-1756; Miyoshi, Shōraku 1696?-1772?; Namiki, Senryū 1695-1751; Keene, Donald (New York Columbia University Press, 1971)
"Chūshingura (The Treasury of Loyal Retainers), also known as the story of the Forty-Six (or Forty-Seven) Rōnin, is the most famous and perenially popular of all Japanese dramas. Written around 1748 as a puppet play, it is now better known in Kabuki performances. In the twentieth century, cinema and television versions have been equally successful. Donald Keene here presents a complete translation of the original text, with notes and an introduction that increase the reader's comprehension and enjoyment of the play. The introduction also elucidates the idea of loyalty. This traditional virtue, as exemplified in Chūshingura, has never completely lost its hold on audiences, in spite of twentieth-century changes in Japanese society and moral ideas. Moreover, as Professor Keene points out, the excitement, color and violence expressed in the play may be considered the counterpoint to the austere restraint and understatement which are more commonly thought to be "traditionally" Japanese."--Page 4 of cover.
Translation of: Kanadehon Chūshingura.
"Prepared for the College Program of Translations from the Asian Classics."
Includes bibliographical references (pages 181-183)
Keywords: Forty-seven Ronin -- Drama; Japan -- Drama